2011 37th IEEE Photovoltaic Specialists Conference 2011
DOI: 10.1109/pvsc.2011.6186440
|View full text |Cite
|
Sign up to set email alerts
|

Centralized vs distributed (power optimizer) PV system architecture field test results under mismatched operating conditions

Abstract: The number of Building Integrated Photovoltaic (BIPV) system installations is increasing as different new and specific solar cells and modules are developed. The great advantages of BIPV systems should be enough to achieve their massive implantation, but the difficult working conditions of the urban environment reduce the energy yield and increase the payback period of investment.In order to boost the energy yield of BIPV systems distributed PV system architectures seem to be the solution. In this sense, TECNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…This topology was considered economic and simplistic as it requires one high power converter operating at a high DC voltage to facilitate grid tied power inversion. However, recent studies have shown that centralized conversion strategies are generally less effective at converting incident sunlight into electricity than the decentralized conversion topologies within urban environments [1]. This is due to their being less current limitation within the smaller multiple stringed systems than with a single stringed system operating under identical conditions.…”
Section: B Decentralized Voltage Conversionmentioning
confidence: 99%
See 1 more Smart Citation
“…This topology was considered economic and simplistic as it requires one high power converter operating at a high DC voltage to facilitate grid tied power inversion. However, recent studies have shown that centralized conversion strategies are generally less effective at converting incident sunlight into electricity than the decentralized conversion topologies within urban environments [1]. This is due to their being less current limitation within the smaller multiple stringed systems than with a single stringed system operating under identical conditions.…”
Section: B Decentralized Voltage Conversionmentioning
confidence: 99%
“…A recent attempt to reduce the partial shading issue involves changing the topology of the PV plant. The most shade robust arrangement is the Module Integrated (MI) topology which involves connecting micro-converter or micro-inverters to each module in the array and a yield in excess of 240% have been reported [1]. This approach allows flexible plant design, lower hardware prices due to mass production and lower minimum array size, however the effectiveness of MI schemes can still be limited as incoherence within a module can still exist.…”
Section: Introductionmentioning
confidence: 99%
“…But, under the condition of mismatch (modules of different output power, shadows, dirtiness, etc. ), this structure of system can led to the problem of mismatch losses [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…1). It can significantly reduce the negative impact of shading panels and increase the efficiency of the whole system by optimizing of operating conditions of each solar panel [3,4].…”
Section: Introductionmentioning
confidence: 99%